Initiation of transthyretin aggregation at neutral pH by fluid agitation - Irina Ritsch; H. Jane Dyson; Peter E. Wright (Proceedings of the National Academy of Sciences, 2025)
The transthyretin (TTR) tetramer, assembled as a dimer of dimers, transports thyroxine and retinol binding protein in blood plasma and cerebrospinal fluid. Aggregation of wild type (WT) or pathogenic variant TTR leads to transthyretin amyloidosis, which is associated with neurodegenerative and cardiac disease. The trigger for TTR aggregation under physiological conditions is unknown. The tetramer is extremely stable at neutral pH, but aggregation via tetramer dissociation and monomer misfolding can be induced in vitro by lowering the pH. To elucidate factors that may cause TTR aggregation at neutral pH, we examined the effect of shear forces such as those that arise from fluid flow in the vascular system. Fluid shear forces were generated by rapidly stirring TTR solutions in conical microcentrifuge tubes. Under agitation, TTR formed β-rich aggregates and fibrils at a rate that was dependent upon protein concentration. The lag time before the onset of agitation-induced aggregation increases as the total TTR concentration is increased, consistent with a mechanism in which the tetramer first dissociates to form monomer that either partially unfolds to enter the aggregation pathway or reassociates to form tetramer. NMR spectra recorded at various time points during the lag phase revealed growth of an aggregation-prone intermediate trapped as a dynamically perturbed tetramer. Enhanced conformational fluctuations in the weak dimer–dimer interface suggest loosening of critical intersubunit contacts which likely destabilizes the agitated tetramer and predisposes it toward dissociation. These studies provide insights into the mechanism of aggregation of WT human TTR under near-physiological conditions.